The Integration of Problem Based Learning Model on Indonesian Language E-Modules - Ni Luh Sukareni; Adrianus I Wayan Ilia Yuda Sukmana (Universitas Pendidikan Ganesha, 2021)
There are still many teachers who have difficulty using technology to develop teaching materials that can facilitate students' learning. This has an impact on student learning outcomes are low. This study aims to develop E-module with problem-based learning model. This type of research is development using the ADDIE model. The subject of the expert test consisted of 3 people, namely 1 subject expert, 1 learning design expert, and 1 learning media expert. The product trial subjects consisted of 9 students. The methods used in collecting data are observation, interviews, and questionnaires. The instrument used in collecting data is a questionnaire. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results of the study were the assessment given by the subject matter expert, which was 96.47 (very good). The assessment of learning design experts is 93.33% (very good). The assessment of learning media experts is 97.5% (very good).Individual trial results, that is 95.53% (very good), and the result of small group trial is 95.53% (very good). It can be concluded that E-modules with problem-based learning models are valid and feasible to be applied in the learning process. The implication of this research is that the E-module with the PBL model can be used by teachers in learning.